Enjoy the Silence: A Discussion Around Players’ Experience and Emotional Accessibility in Alice is Missing (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2024)
In this paper, we examine how the silent role-playing game Alice is Missing structures an accessibility framework focused on minority representation and safe space regarding sensitive topics while questioning the limits posed by its archetypal setting. Thus, we consider accessibility through the means it deploys to welcome a variety of players and the way its safety tools can foster emotional experiences. We analyze this game using its own frame: a textual exchange. The idea is to recapture our experience during the game by reproducing the text dialogue structure we were offered. This approach is rooted in the idea of dialogism as a point of encounter and synthesis of individual realities and in what seems to us one of the central propositions of Alice is Missing, that is, a collaborative creative experience that aims to respect each participants’ individuality.